CFM1, a member of the CRM‐domain protein family, functions in chloroplast group II intron splicing in Setaria viridis. (11th December 2020) - Feiz, Leila; Asakura, Yukari; Mao, Linyong; Strickler, Susan R.; Fei, Zhangjun; Rojas, Margarita; Barkan, Alice; Stern, David B.
SUMMARY: The chloroplast RNA splicing and ribosome maturation (CRM) domain is a RNA‐binding domain found in a plant‐specific protein family whose characterized members play essential roles in splicing group I and group II introns in mitochondria and chloroplasts. Together, these proteins are required for splicing of the majority of the approximately 20 chloroplast introns in land plants. Here, we provide evidence from Setaria viridis and maize that an uncharacterized member of this family, CRM Family Member1 (CFM1), promotes the splicing of most of the introns that had not previously been shown to require a CRM domain protein. A Setaria mutant expressing mutated CFM1 was strongly disrupted in the splicing of three chloroplast tRNAs: trnI, trnV and trnA . Analyses by RNA gel blot and polysome association suggest that the tRNA deficiencies lead to compromised chloroplast protein synthesis and the observed whole‐plant chlorotic phenotypes. Co‐immunoprecipitation data demonstrate that the maize CFM1 ortholog is bound to introns whose splicing is disrupted in the cfm1 mutant. With these results, CRM domain proteins have been shown to promote the splicing of all but two of the introns found in angiosperm chloroplast genomes. Significance Statement: The CRM proteins are a plant‐specific family of RNA‐binding proteins that are involved in intron splicing in chloroplasts and mitochondria. We describe the role of a previously uncharacterized member, CFM1, in chloroplast group II intron splicing in Setaria viridis .